PENGUATAN KARAKTER PEDULI LINGKUNGAN UNTUK MEWUJUDKAN PENDIDIKAN KEWARGANEGARAAN GLOBAL PADA PESERTA DIDIK DI SMA WACHID HASYIM 2 TAMAN SIDOARJO - Mirza Nuriyah Fahma; Listyaningsih (Universitas Negeri Surabaya (Unesa), 2025)
Strengthening environmental character through several processes is important in forming students who are responsible for the environment. The purpose of this study is to describe the process of strengthening environmental character to realize global citizenship education for students at SMA Wachid Hasyim 2 Taman. The theory used in this study is the theory of global citizenship education. There are three dimensions including knowledge (cognitive), attitudes (socio-emotional), and skills (psychomotor). The research method used is qualitative research. Data collection techniques used observation, semi-structured interviews, and documentation. The research subjects were the vice principal for student affairs, the SDGs team coordinator, and members of the SDGs team. The data analysis technique used analysis by Miles and Huberman. The results of the study indicate that strengthening environmental character at SMA Wachid Hasyim 2 Taman Sidoarjo is through several processes. These processes are through contextual learning in the classroom, P5 activities, the SDGs team, and the SHW (Waqf Forest School) community. Through these processes, students become more aware of protecting and preserving the environment. This is evidenced by students cleaning their classrooms without being reminded, caring for the plants around the school, actively participating in environmental activities voluntarily, and reminding each other to work together to protect the environment. This is related to global citizenship education, which instills the values of responsibility and care for environmental issues and creates a sustainable environment.